Pensar em tempos sombrios: As implicações políticas do pensamento na perspectiva de Hannah Arendt - Rocha, Lara França da (2019)
The experience of dark times led Hannah Arendt to the need to investigate what thought would be and how this faculty manifests itself in the sphere of human affairs. Identifying that dismantling metaphysical fallacies is a sine qua non condition for understanding this spiritual activity differently from the philosophical abyss erected between active vita and contemplative vita, the author pointed out that the break with tradition, while conferring inability to research on thinking , also requires that this reflection be answered starting from a phenomenological reconstruction of the activities of the spirit. In fact, the recovery of the dignity of politics unequivocally permeates the recovery of the dignity of thought, considering it not as a faculty distant from reality and the experiences of individuals, but as the possibility of research on the world and on itself without to which no plural existence is fully realized. Thus, in order to answer the question of what it means to think of boundary situations, or what the thinking ego's place in the face of the political and moral collapse that undermines the modern world, it is necessary, at first, to analyze the Arendtian concept of dark times, relating it to alienation and totalitarianism as an unprecedented form of government that radicalized both the degradation of politics and the obscurity of the public scene. Next it is necessary to understand what the Arendtian definition of thought is, identifying how it differs from cognition as well as the modus operandi of its exercise, mainly from metaphor and imagination. Soon after, the political implications of this mental activity will be analyzed, starting from the non-thinking forged by the ideology until reaching how the sensus communis relates as much to the maintenance of the world as to the thinking. In this sense, the figure of Socrates is based as the paradigm of the reflective citizen who, far from disassociating thought and public space, considered that the investigation promoted by the thinking ego would be the greatest benefit achieved by the polis. Finally, we will examine the ability to judge, the way in which thinking is revealed in the coexistence between men, identifying why Arendt considered the political faculty par excellence, as well as underlining the relation between judgment and responsibility for the world and the importance of examples.